Etika dan Ketidakjujuran Akademik di Perguruan Tinggi - Desy Annisa Nugraha; Nurhayati Fitrie; Ela Nurlaila; In In Supianti; Bana G. Kartasasmita; Asep Sahrudin (Universitas Mathla'ul Anwar Banten, 2020)
The existence of the phenomenon of academic dishonesty is increasingly entrenched among college students. A prestige achievement of high scores in each exam affects students to cheat answers from friends / notes / other sources (internet). This is in contradiction with academic ethics. The purpose of this study was to determine the percentage of mathematics students who committed academic dishonesty and the types of academic dishonesty they did, as well as the reasons for doing academic dishonesty. The research method used was a literature review and a description of the results of the questionnaire and interviews of 39 graduate students consisting of 16 men and 23 women. The questionnaire consisted of 24 statements regarding the type of academic dishonesty. From the results of the questionnaire, it was found that the most widely done was to collaborate on a specific lecture assignment, or take-home test, which was instructed to be done alone (90%). Followed by whispering answers to exam questions to friends while taking the exam together (82%) and quoting verbatim from a source of writing and I submit the quote as fulfillment of my college assignments (82%). Based on the results, efforts are needed to prevent and eradicate academic dishonesty. Keywords: academic dishonesty, academic ethics, cheating